Effect of Dietary Protein Intake on Bone Mineral Density and Fracture Incidence in Older Adults in the Health, Aging, and Body Composition Study. (3rd March 2021) - Weaver, Ashley A; Tooze, Janet A; Cauley, Jane A; Bauer, Douglas C; Tylavsky, Frances A; Kritchevsky, Stephen B; Houston, Denise K
Abstract: Background: Dietary recommendations may underestimate the protein older adults need for optimal bone health. This study sought to determine associations of protein intake with bone mineral density (BMD) and fracture among community-dwelling White and Black older adults. Method: Protein as a percentage of total energy intake (TEI) was assessed with a Food Frequency Questionnaire in 2160 older adults (73.5 ± 2.8 years; 51.5% women; 35.8% Black) in the Health, Aging, and Body Composition prospective cohort. Hip, femoral neck, and whole body BMD was assessed by dual-energy x-ray absorptiometry at baseline and 4 years, and lumbar trabecular, cortical, and integral BMD was assessed by computed tomography at baseline and 5 years. Fragility fractures over 5 years were adjudicated from self-report data collected every 6 months. Associations with tertiles of protein intake were assessed using analysis of covariance for BMD and multivariate Cox regression for fracture, adjusting for confounders. Results: Participants in the upper protein tertile (≥15% TEI) had 1.8%–6.0% higher mean hip and lumbar spine BMD compared to the lower protein tertile (<13% TEI; p < .05). Protein intake did not affect change in BMD at any site over the follow-up period. Participants in the upper protein tertile had a reduced risk of clinical vertebral fracture over 5 years of follow-up (hazard ratio: 0.36 [95% confidence interval: 0.14, 0.97] vs lower protein tertile, p = .04). Conclusions: Older adults with higher protein intake (≥15% TEI) had higher BMD at the hip, whole body, and lumbar spine, and a lower risk of vertebral fracture.